Cuentos Infantiles en el desarrollo del lenguaje oral de los niños y niñas de Primer Año de la escuela de Educación Básica “Capullitos, provincia de Chimborazo, periodo mayo– octubre 2021 - Contento Salazar, Maryuri Alexandra (2022)
This research identifies a problem of coexistence in the first-year children of the "capullitos" primary education school, province of Chimborazo, May-October 2021. This is why it is proposed from the theoretical point of view a solution through the study of emotional intelligence and its contribution to the development of interpersonal relationships of human beings. A methodology with a qualitative approach was used to carry out this research, of a descriptive type with a non-experimental design and a bibliographic level. The survey and observation technique were applied; As instruments, the questionnaire and the observation sheet were used to collect information. The main results were to define emotional intelligence as a determining factor for the coexistence of children. In turn, through observation, it was possible to appreciate the levels of development of emotional intelligence and thus propose strategies to improve the coexistence of this population. The discussion arises in the existing discrepancies in the levels analyzed, such as games, participatory classes, and their reflection. Therefore, it verified that, in case of wanting to propose strategies, these should be focused on the most deficient levels. A conclusion is that it is vital to contribute to improving emotional intelligence since, through this, it will be possible to stimulate children to adapt to a dynamic society with an acceptable coexistence.